دور تكنولوجيا البلوكشين في رقمنة التحاسب الضريبي وانعكاساتها على الامتثال الضريبي: دراسة ميدانية - فاضل، أحمد محمد إبراهيم; أبو الخير، محمد حارس محمد طه (جامعة المنوفية - كلية التجارة, 2023)
باتت تكنولوجيا البلوكشين واحدة من أهم تقنيات الثورة الصناعية الرابعة، التي تستهدف رقمنة كل شيء، فقد توسعت تطبيقاتها ولاتزال تتطور في السنوات الأخيرة، ولم تعد محصورة في مجال التحويلات المالية الرقمية فقط، وأصبحت تستخدم في العديد من المجالات، لذا يهدف هذا البحث إلى فحص دور تكنولوجيا البلوكشين في رقمنة التحاسب الضريبي، وانعكاساتها على الامتثال الضريبي، ولتحقيق هذا الهدف تم الاعتماد على المنهج الوصفي القائم على مراجعة الدراسات السابقة واستطلاع آراء عينة حجمها (۹۸) مفردة من قطاع الحاسب ونظم المعلومات والتحول الرقمي بمصلحة الضرائب وشركة تكنولوجيا تشغيل الحلول الضريبية E-Tax، وقد أشارت نتائج البحث إلى أن السمات المميزة لتكنولوجيا البلوكشين يمكن أن تساعد في رقمنة التحاسب الضريبي، بما ينعكس إيجابيا على مستوى الامتثال الضريبي، من حيث تحسين الشفافية الضريبية، وتعزيز الخصوصية والسرية الضريبية في نفس الوقت، وتحسين مستوى الدقة وإزالة التقدير الجزافي، وزيادة كفاءة التحصيل الضريبي وتحسين نظام الفحص الضريبي، وتخفيض تكاليف الامتثال الضريبي، وإمكانية فرض الضرائب على أنشطة الاقتصاد الرقمي، ومع ذلك توجد بعض التحديات القانونية والتنظيمية ومعوقات التشغيل البيئي ومعوقات التكلفة التي قد تحول دون تبنى الإدارات الضريبية لهذه التكنولوجيا، وفي ضوء هذه النتائج يوصى الباحثان مصلحة الضرائب المصرية بالسعي نحو اعتماد تكنولوجيا البلوكشين في رقمنة مجالات التحاسب الضريبي، وأن يتم تقييمها مثل أي حل تقني آخر لرقمنة التحاسب الضريبي، وعلى خبراء الضرائب تنمية مهاراتهم الرقمية لمواكبة ذلك. Blockchain technology has become one of the most important technologies of the fourth industrial revolution, which aims to digitize everything. Its applications have expanded and continue to evolve in recent years, and it is no longer limited to digital financial transactions only. It is now used in many fields. This research aims to examine the role of blockchain technology in digitizing tax accounting and its impact on tax compliance. To achieve this goal, a descriptive approach was adopted based on literature review and surveying the opinions of a sample of 98 individuals from the computer, information systems, digital transformation sector in tax authorities, and E Tax, a tax technology solutions company. The research results indicated that the distinctive features of blockchain technology can help digitize tax accounting, which positively reflects on tax compliance. This is achieved by improving tax transparency, enhancing tax privacy and confidentiality at the same time, improving accuracy levels and eliminating arbitrary estimation, increasing tax collection efficiency, improving the tax audit system, reducing tax compliance costs, and enabling the taxation of digital economy activities. However, there are some legal and regulatory challenges, environmental operating obstacles, and cost barriers that may hinder tax authorities from adopting this technology. In light of these results, the researchers recommend that the Egyptian tax authority should adopt blockchain technology in digitizing tax accounting and evaluate it like any other technological solution for digitizing tax accounting. Tax experts should also develop their digital skills to keep up with these changes.
Keywords: تكنولوجيا البلوكشين -- الاقتصاد الرقمي -- التحاسب الضريبي -- الشفافية الضريبية